2016
DOI: 10.3390/molecules21040430
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anti-Oxidant and Anti-Inflammatory Effects between Fresh and Aged Black Garlic Extracts

Abstract: Numerous studies have demonstrated that aged black garlic (ABG) has strong anti-oxidant activity. Little is known however regarding the anti-inflammatory activity of ABG. This study was performed to identify and compare the anti-oxidant and anti-inflammatory effects of ABG extract (ABGE) with those of fresh raw garlic (FRG) extract (FRGE). In addition, we investigated which components are responsible for the observed effects. Hydrogen peroxide (H2O2) and lipopolysaccharide (LPS) were used as a pro-oxidant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 48 publications
3
95
1
4
Order By: Relevance
“…FG has long been considered as a medicinal food with antibacterial, antiviral, antidiabetic, antioxidant, anti‐inflammatory, anti‐hypertensive, cardioprotective, hypolipidemic, and immune‐boosting effects due to its high content of OSC (Bayan, Koulivand, & Gorji, ). The processing of FG into BG induces alterations in biological activities due to the fermentation‐induced changes in bioactive compounds, for example, increased antioxidant activities (including the abilities to scavenge 2,2‐azinobis‐(3‐ethylbenzothiazoline‐6‐sulfonate) [ABTS], 1,1‐diphenyl‐2‐picrylhydrazyl [DPPH], and hydroxyl radicals as well as reducing power) (Jeong et al., ; Kim, Nam, et al., ), but reduced immunomodulatory activity of BG as compared with FG (Li et al., ). There exist a number of published reviews or book chapters on the bioactivities of BG.…”
Section: Nutritional Value and Biological Activity Of Bgmentioning
confidence: 99%
See 2 more Smart Citations
“…FG has long been considered as a medicinal food with antibacterial, antiviral, antidiabetic, antioxidant, anti‐inflammatory, anti‐hypertensive, cardioprotective, hypolipidemic, and immune‐boosting effects due to its high content of OSC (Bayan, Koulivand, & Gorji, ). The processing of FG into BG induces alterations in biological activities due to the fermentation‐induced changes in bioactive compounds, for example, increased antioxidant activities (including the abilities to scavenge 2,2‐azinobis‐(3‐ethylbenzothiazoline‐6‐sulfonate) [ABTS], 1,1‐diphenyl‐2‐picrylhydrazyl [DPPH], and hydroxyl radicals as well as reducing power) (Jeong et al., ; Kim, Nam, et al., ), but reduced immunomodulatory activity of BG as compared with FG (Li et al., ). There exist a number of published reviews or book chapters on the bioactivities of BG.…”
Section: Nutritional Value and Biological Activity Of Bgmentioning
confidence: 99%
“…Antioxidant activity is the most prominent characteristic of BG. In vitro studies revealed that BG had high DPPH radical, ABTS radical, hydroxyl radical, nitrite radical, and superoxide anion radical scavenging activities; ferric reducing antioxidant power; and trolox equivalent antioxidant capacity (Jeong et al, 2016;Jung & Sohn, 2014;Kim, Nam, et al, 2012;Lee et al, 2009;Zhang et al, 2015). BG was also found to inhibit strongly lipid peroxidation (linoleic acid peroxidation) and free radical production (Fe 2+ -chelating ability), and exhibit reducing power (potassium ferricyanide reduction) and SODlike activity (Bae et al, 2014;Kim, Nam, et al, 2012;Sato, Kohno, Hamano, et al, 2006).…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…After the thermal process, there was a decrease in fructan content, although there was an increase in total water‐soluble sugar content and Maillard reaction intermediates in black garlic (Yuan and others ). And it was indicated from previous reports that black garlic had stronger antioxidant activity than that of fresh garlic due to high amounts of organosulfur compounds (Jeong and others ). However, it was demonstrated that ethanolic extracts of black garlic exerted a relatively weak antiallergic activity compared with that of fresh garlic (Kim and others ).…”
Section: Introductionmentioning
confidence: 96%
“…Also, it is available on the markets in the form of whole bulbs, powder, or organic capsules (Kim et al, 2011). ABG was found to show more antioxidant activity and higher content of total polyphenol than fresh garlic Shin, Choi, Lee, Cha, & Sung, 2008;Jeong et al, 2016). Aged black garlic also has been largely attributed to as having cardioprotective, antidiabetic, hepatoprotective, antimicrobial, antioxidant, anti-inflammatory, antithrombotic, antihypertensive, and antihyperlipidemic properties.…”
Section: Introductionmentioning
confidence: 99%